PENGARUH MODEL PEMBELAJARAN MISSOURI MATHEMATICS PROJECT (MMP) TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA KELAS X SMAS GKPI PADANG BULAN - Saputri Silitonga; Denny Haris (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine whether the Missouri Mathematics Project (MMP) learning model affects high school students’ mathematical problem-solving abilities. The research is classified as a quasi-experimental study. The population consisted of all Grade X students at SMAS GKPI Padang Bulan, with class X-3 as the experimental group and class X-2 as the control group. The experimental class was taught using the MMP model, while the control class received conventional instruction. The test instrument consisted of three valid essay questions for both the pretest and posttest. Based on the pretest results, the experimental class had an average score of 49.10, while the control class scored 50.51. After the treatment, the experimental class obtained an average posttest score of 84.23, compared to 64.62 in the control class. Statistical analysis revealed that the data were normally distributed and linear, enabling hypothesis testing. Simple linear regression produced the equation Ŷ = 31.713 + 0.770X. Based on the hypothesis test, = , at a significance level of α = 0.05 and = 2,064. Since and the significance value was 0.000 < 0.05, was rejected and was accepted. This indicates that the MMP learning model has a significant effect on students' mathematical problem-solving abilities. The R-square value was 0.412, meaning that 41.2% of the improvement was influenced by the MMP model, while the remaining 58.8% was influenced by other factors not included in the study.